Pediatric Blepharoptosis - Jubbal, Kevin T.; Kania, Katarzyna; Braun, Tara L.; Katowitz, William R.; Marx, Douglas P. (Seminars in Plastic Surgery, 2017)
Congenital blepharoptosis, caused by levator muscle dysgenesis, presents at birth and may lead to disturbed visual development and function. Other causes of ptosis in pediatric patients can be myogenic, neurogenic, mechanical, or traumatic. Timely correction is, therefore, critical, and careful preoperative planning and intraoperative considerations are crucial to achieve optimal outcomes and minimize potential complications. The various surgical techniques, including the frontalis suspension or sling, levator resection and advancement, Müller's muscle conjunctival resection (the Putterman procedure), and modified Fasanella-Servat procedure are each associated with distinct indications, benefits, and drawbacks, necessitating a unique tailored approach to each surgical candidate.
Keywords: pediatric ptosis; blepharoptosis; droopy eyelid